The Socio-Economic Context of the Rohingya-Rakhine Communities’ Conflict in Myanmar, 1942-2024 - Thaddeus T. Ityonzughul; Preye Adekoya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
The Rohingya-Rakhine communities’ conflict in Myanmar has been a protracted and complex issue since the 1970s, fueled by historical animosity, religious and social differences, and competition for resources. The conflict has led to significant humanitarian crises, including mass displacement, human rights abuses, and severe food shortages, with 57 percent of families in Rakhine State unable to afford basic food needs. The situation has been exacerbated by the February 2021 military coup, with both the Myanmar military and the Arakan Army committing human rights abuses. Using secondary sources of data and interdisciplinary approach, this paper explores the socio-economic context of the conflict, examining the historical context, current situation, and potential solutions to address the humanitarian crisis and promote sustainable peace and development. It aims to contribute to a deeper understanding of the conflict and identify effective strategies for resolving it. The paper highlights the need for a comprehensive and inclusive approach that addresses the root causes of the conflict and promotes the rights and dignity of all communities involved. Ultimately, this paper seeks to inform policy and practice aimed at promoting peace, stability, and human rights in Myanmar.